The air quality in narrow two-dimensional urban canyons with pitched and flat roof buildings. (2017) - Ferrari, Simone; Badas, Maria Grazia; Garau, Michela; Seoni, Alessandro; Querzoli, Giorgio
The aim of this paper is the study of the air quality in narrow urban canyons (ratio of the distance between two buildings to the building height less than or equal to one). This has been done by investigating two key points. The first one is the investigation of the modifications that the roof shape induces in the flow and turbulence, through the comparison of velocity fields, turbulence characteristics and air exchanges between the urban canyon and the outer flow in arrays of buildings with flat and pitched roofs. The second one is the assessment of the capability of a RANS model to correctly simulate the flow, through the comparison with laboratory water-channel simulations. Among the analysed quantities, the vertical air exchange rate ACH measures the rate of air removal from a street canyon. Results show that the pitched roof strongly modifies the flow and increases the turbulence and the air exchange between the canyon and the external flow, highlighting how the choice of the roof shape can be meaningful for building design, planning strategies and regulatory purposes.